Determination of the mechanical, thermal, transport, electronic and optoelectronics properties of AMoO4 (A=Ca, Sr, Ba, Pb), with and without oxygen vacancy, by ab-initio calculations - Pecinatto, Henrique (Universidade Federal do Amazonas, 2023)
Molybdates of the form AMoO 4 (A = Ca, Sr, Ba, Pb) are widely studied materials due to their photo-luminescence properties. In the present doctoral thesis, we analyze the effect of oxygen vacancies through density functional density (DFT) in these scheelite-type materials, aiming primarily at the possible ferromagnetism induced due to this kind of defect. The spin- polarized band structure spectrum shows the appearance of narrow bands within the band gap for the spin-up channel. In BaMoO 4 -V O × , SrMoO 4 -V O × , and PbMoO 4 -V O × a resultant magnetic moment of 2µ B per cell is observed due to, the electrons once bonded with O being trapped by the 4d states in trigonal cluster MoO 3 , while in CaMoO 4 -V O × , the oxygen vacancy distort the lattice, so that crystal field splitting results in a low spin case with the resultant magnetic moment of 0.15µ B per cell. This study also provides a valuable tool for lowering the band gap in these materials, since the wide band gap has been recognized as a challenging factor for infrared and visible light photocatalysis performance. We calculated the mechanical properties from elastic constants such as bulk, shear, and Young modulus. In addition, Vicker’s hardness indicates that oxygen vacancy increases the hardness of these materials. For thermoelectric properties, the electrical conductivity is addressed to the n-type carrier and, allied with the low thermal conductivity (lattice + electronic) provided by phonon scattering, results in a high figure of merit for all defective scheelites.